Modeling of Gear Transmission System and Analysis of Dynamic Response Characteristic - Zhu Yun; You Qiangqiang (Jixie chuandong)
The dynamic modeling for gear transmission system is studied for solution of the problems relating to the reliability of dynamic response characteristics analysis in gearboxes. A one-dimensional finite element model of gear transmission system is created by using lumped parameter method. The stiffness and mass matrices of total degrees of freedom are established for axes based on the theory of Timoshenko Beam and material mechanics theory. And the damping matrix is determined by a given modal damping coefficient. An additional stiffness matrix is established in consideration of the effect of gear coupling and bearing stiffness. The dynamic response of bearing is calculated by using dynamic flexibility method in combination of the dynamic meshing force obtained from the calculation of transmission error of a meshed gear pair and the dynamic meshing stiffness,which is used as the exiting force to be derived in dynamic equations. The result of bearing dynamic response is analyzed based on this mentioned modeling method for a certain type of gearbox. Comparison is made with the result from bench test and both are in good consistence. It proves the reliability of this modeling theory and provides the basis for the optimization of gearboxes in initial design.